PROBIOTICS IN THE PREVENTION OF RECURRING RESPIRATORY INFECTIONS IN CHILDHOOD: EFFICACY AND IMPACTS (REMUNOM, 2024)
Introduction: Respiratory Tract Infections (RTIs) are among the most common disorders in pediatrics and the main causes of morbidity and mortality worldwide. In approximately 15% of children, these infections are recurrent, affecting their quality of life and that of their families, in addition to the social impacts and costs generated to the public coffers, requiring resolute interventions to reduce their recurrence. Objective: To evaluate the efficacy of probiotics in the prevention of Recurrent Respiratory Infections (RRI) and their impacts. Method: This is an Integrative Literature Review, carried out in six stages, using the descriptors in health sciences, in English, combined as follows